PSO based Adaptive Force Controller for 6 DOF Robot Manipulators - Thunyajarern, Sutthipong; Seeboonruang, Uma; Kaitwanidvilai, Somyot (Lecture notes in engineering and computer science, 2017)
Force control in robot arm has been used in many industrial applications especially end-effector contacting with environment. When environment is change, the performance of non-adaptive controller may be decreased. This paper presents adaptive force controller for 6 DOF (degree of freedom) Robot Manipulators that do not require identifying the environment before controlling. Particle swarm optimization (PSO) has been employed to solve this problem. In simulation, the end-effector was moved and touched different environments. The simulation results were compared with typical non-adaptive control. The result shows that when the environment is changed, the performance of non-adaptive force controller decreased. On the other hand, the performance of PSO based adaptive force controller remained the same.